A numerical study of the contact geometry and pressure distribution along the glenoid track. (December 2022) - Junior, Alexandre Neves Trichez; Pécora, José Otávio Reggi; Neto, Arnaldo Amado Ferreira; Roesler, Carlos Rodrigo de Mello; Fancello, Eduardo Alberto
Highlights: Non-spherical incongruent joint surfaces. Contact mechanics and pressure distribution along the glenoid track. Deformable-to-deformable contact surfaces. Humeral head translation. Abstract: The glenoid track geometry and the contact forces acting on the glenohumeral joint at static positions of 30°, 60°, 90° and 120° of abduction with 90° of external rotation were evaluated using a finite element model of the shoulder that, differently from most usual approximations, accounts the humeral head translations and the deformable-to-deformable non-spherical joint contact. The model was based on data acquired from clinical exams of a single subject, including the proximal humerus, scapula, their respective cartilages concerning the glenohumeral joint, and the rotator cuff and deltoid muscles. The forces acting on the glenohumeral joint were estimated using a simulation framework consisting of an optimization procedure allied with finite element analysis that seeks the minimum muscle forces that stabilize the joint. The joint reaction force magnitude increases up to 680.25 N at 90° of abduction and decreases at further positions. From 60° onward the articular contact remains at the anterior region of the glenoid cartilage and follows an inferior to superior path at the posterior region of the humeral head cartilage. The maximum contact pressure of 3.104 MPa occurs at 90° abduction. Although translating inferiorly throughout the movement, the projection of the humeral head center at the glenoid plane remains at the central region of the glenoid surface. The model results qualitatively matched the trends observed in the literature and supports the consideration of the translational degrees of freedom to evaluate the joint contact mechanics.